PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN PBL BERBANTU MEDIA BENDA KONKRET PADA SISWA KELAS 4 SD - Sri Wahjoeningsih; Meirza Nanda Faradita; Iswahyuni (PROCEEDING UMSURABAYA, 2024)
Improving the quality of education and developing the learning process is a problem that always demands attention. Mathematics learning outcomes will be obtained if there has been a learning process shown through creativity and learning models designed by teachers. The Problem Based Learning learning model is expected to be able to help students to get used to solving and analyzing a problem so that students' problem solving skills will be maximally formed. This research was conducted at Hang Tuah 12 Surabaya Elementary School in class 4 semester I of the 2023/2024 academic year with material thinking about how to count numbers. The research method used is a qualitative model obtained from the results of student evaluation and observation.comparison of research results from the first cycle with the second cycle to determine the success and shortcomings of the research with the benchmark for achieving KKM. The results of the study to determine the improvement of mathematics learning outcomes through PBL learning assisted by concrete object media in 4th grade elementary school students through 2 cycles as a comparison. In cycle 1 with 23 students, the highest score was 80, and the lowest score was 55, so the class average was 68. These results show 10 students (43%) have been completed, and 13 students (57%) who have not been completed. Meanwhile, in cycle 2 with 23 students, the highest score was 95, and the lowest score was 80, so the class average was 87. These results show 23 students (100%) have been completed and none have not been completed. The results obtained can be concluded that learning using the Problem Based Learning model assisted by concrete object media in grade 4 elementary school students can improve learning outcomes and make student scores complete or above KKM.